Real-time observation of the thermally-induced phase transformation in GeTe and its thermal expansion properties - Tran, Xuan Quy; Hong, Min; Maeno, Hiroshi; Kawami, Youichirou; Toriyama, Takaaki; Jack, Kevin; Chen, Zhi-Gang; Zou, Jin; Matsumura, Syo; Dargusch, Matthew S. (Acta materialia, 2019)
The GeTe-based system has long been considered as a promising candidate system for various functional applications; many of which are directly related to the polymorphic phase transformation in their crystalline forms. Consequently, the microstructure underlying their intriguing phase transition has been the subject of numerous studies. Here we provide real-time observation of the microstructural changes associated with the reversible pseudo-cubic (or rhombohedral) to cubic GeTe phase transition using high-voltage transmission electron microscopy (HV-TEM) operating at 1,250 kV and complementary high-temperature X-ray diffraction (XRD). As a result of the phase transition, the pseudo-cubic GeTe domain's configuration significantly changes from its original band-like to a spike-like morphology with a different orientation after a heating/cooling cycle. The coefficients of thermal expansion (CTE) properties as a function of temperature are also explored in relation to the GeTe phase transition. [Display omitted]